The earliest Christologies : five images of Christ in the postapostolic age - Papandrea, James L., 1963- (Downers Grove, IL : IVP Academic, An imprint of InterVarsity Press, 2016)
In this clear and concise introduction to second-century christologies, James Papandrea sets out five of the principal images of Christ that dominated the postapostolic age. Between varieties of adoptionism and brands of Gnosticism, Papandrea helps us see how Logos Christology was forged as the beginning of the church's orthodox confession.
Images of Christ in the postapostolic age -- Christ as angel: angel adoptionism -- Christ as prophet: spirit adoptionism -- Christ as phantom: docetism and docetic gnosticism -- Christ as cosmic mind: hybrid gnosticism -- Christ as word: logos Christology -- What, then, is orthodoxy?
Includes index.
Description based on print version record and CIP data provided by publisher.
Includes bibliographical references and indexes.
English.
Master record variable field(s) change: 050
Keywords: Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Jesus Christ; RELIGION -- Christian Theology -- Christology; Theology, Doctrinal; Christianity; Religion; Philosophy & Religion; 30-600; Electronic books; History